Crop Establishment Methods and Micro Irrigation for Enhancing Productivity of Total System and Water in Rice-Wheat Cropping System in Haryana: An On-Farm Study - Bhardwaj, A. K.; Soman, P.; Sharma, Neeraj; Pandiaraj, T.; Labh, B. K. (European Journal of Applied Sciences, 2022)
Rice-wheat cropping system (RWCS) is sustenance for the majority of people in India contributing food security to the nation. However, in the past two decades, water shortage is a serious constraint to nourishing and increasing the productivity of RWCS. Many technological interventions such as raised seed beds, direct seeding, mechanical planting, laser levelling of the land, etc., have been tried to save a significant amount of water. Of which, micro irrigation offers a promising technology on water saving. Therefore, an experiment was conducted to evaluate the grain yield and water productivity of rice-wheat rotation system under different crop establishment and irrigation methods. The treatment consists of three different methods of establishment (i.e., i. direct seeded rice, DSR/Zero tillage, ZT in wheat; ii. mechanical transplanting for rice/Happy seeder for wheat; iii. Manual method) and three irrigation systems (i.e., i. conventional flood irrigation; ii. Drip; iii. Sprinkler irrigations) along with farmers’ practice. This study was carried out for three years from 2018-19 to 2020-21 as on farm study at Gumthala Garhu village, Pehowa of Kurukshetra district, Haryana, India. The manual planting method recorded 7.8% more rice yield and 1.3% more wheat yield over DSR/ZT. The yield advantage due to drip irrigation over flood irrigation method was 10.27% and 2.24% in rice and wheat, respectively. The manually planted crop (11827 kg ha-1) exerted a significant effect on TSP and on an average a 105% productivity enhancement was recorded over the DSR/ZT (11263 kg ha-1) among the establishment methods. Drip irrigation (11970 kg ha-1) resulted in 106.69% productivity enhancement of RWCS over flood irrigation (11219 kg ha-1). Physical water productivity (PWP) and economic water productivity (EWP) for irrigation water use (IWU) and total consumptive water use (TCWU) of manual planting and drip irrigation were superior to other practices in the total system. AS for water use, manual establishment method recorded 14% less water use over DSR/ZT. Similarly, drip irrigation could save 41% and sprinkler irrigation 37% water over that in flood irrigation method. Therefore, micro irrigation could be a sound technology for water saving in RWCS, thus allowing sustainable food grain production in water scarcity regions.